2021
DOI: 10.1002/anie.202113278
|View full text |Cite
|
Sign up to set email alerts
|

Ordered PtFeIr Intermetallic Nanowires Prepared through a Silica‐Protection Strategy for the Oxygen Reduction Reaction

Abstract: Developing efficient and stable Pt‐based oxygen reduction reaction (ORR) catalysts is a way to promote the large‐scale application of fuel cells. Pt‐based alloy nanowires are promising ORR catalysts, but their application is hampered by activity loss caused by structural destruction during long‐term cycling. Herein, the preparation of ordered PtFeIr intermetallic nanowire catalysts with an average diameter of 2.6 nm and face‐centered tetragonal structure (fct‐PtFeIr/C) is reported. A silica‐protected strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…In particular, templating and protective layer coating methods have successfully produced multidimensional intermetallic nanoarchitecture from onedimensional (1D) nanostructures to three-dimensional (3D) skeletal nanomaterials. 11,[22][23][24][25][26][27]32 1D nanomaterials, including NWs, nanorods, and nanotubes, have emerged as promising electrocatalytic nanostructures owing to their high surface-area-to-volume ratio and electrical conductivity. In addition, their anisotropy enables multiple contacts with the surface of the electrode or support materials, ACS Nanoscience Au resulting in improved stability against aggregation of nanostructure or detachment from the electrode surface compared to the 0D nanocrystals.…”
Section: Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, templating and protective layer coating methods have successfully produced multidimensional intermetallic nanoarchitecture from onedimensional (1D) nanostructures to three-dimensional (3D) skeletal nanomaterials. 11,[22][23][24][25][26][27]32 1D nanomaterials, including NWs, nanorods, and nanotubes, have emerged as promising electrocatalytic nanostructures owing to their high surface-area-to-volume ratio and electrical conductivity. In addition, their anisotropy enables multiple contacts with the surface of the electrode or support materials, ACS Nanoscience Au resulting in improved stability against aggregation of nanostructure or detachment from the electrode surface compared to the 0D nanocrystals.…”
Section: Nanostructuresmentioning
confidence: 99%
“…11 In another Zhang and co-workers developed intermetallic PtFeIr NWs possessing an fct crystal structure (fct-PtFeIr/C) with a diameter of 2.6 nm using silica protective layers. 22 To form silica protective layers on the catalyst, the asprepared PtFeIr NWs with an alloy fcc phase (fcc-PtFeIr/C) was mixed with ethanol and ammonium hydroxide. Then, tetraethylorthosilicate (TEOS) was added to the mixture, and the mixture was stirred for 12 h. Finally, after the annealing process at 690 °C for 2 h and subsequent silica removal, the fct-PtFeIr/C was formed.…”
Section: Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…( Chung et al, 2015 ; Liu et al, 2015 ) Third, the highly fct -ordered structure and strong d -interaction between Fe and Pt tends to be stable, especially the reaction of Fe and Pt in acidic solutions. ( Hu et al, 2020 ; Yang et al, 2022 ) However, it is worth noting that metal leaching occurs under high-potential electrochemical conditions. Previous simulation studies have shown that in the fct -PtFe structure, Fe and Pt interact strongly through spin-orbit coupling, and the hybridization of Fe 3 days and Pt 5 days states makes the chemical structure of fct -PtFe more stable.…”
Section: Ordered Pt-based Intermetallic Compoundsmentioning
confidence: 99%
“…For this reason, the rotation electrode technique, including rotating disk electrode (RDE) and rotating ring disk electrode (RRDE), has been the most common way to obtain the intrinsic activities of ORR catalysts. [13][14][15][16] The Koutecky-Levich (K-L) equation describes current density of electrocatalysts on RDE (Eq. S1-3).…”
Section: Introductionmentioning
confidence: 99%